1997
DOI: 10.1099/0022-1317-78-4-747
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for quasispecies populations during persistence of the coronavirus mouse hepatitis virus JHM: sequence conservation within the surface glycoprotein gene S in Lewis rats.

Abstract: The surface glycoprotein S (spike) of coronaviruses is believed to be an important determinant of virulence and displays extensive genetic polymorphism in cell culture isolates. This led us to consider whether the observed heterogeneity is reflected by a quasispecies distribution of mutated RNA molecules within the infected organ. Coronavirus infection of rodents is a useful model system for investigating the pathogenesis of virus-induced central nervous system (CNS) disease. Here, we investigated whether gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, no specific mutation was necessary for the establishment of in vivo persistence (66), even though a variety of mutations in the N and S genes was observed in mice, suggesting the development of quasispecies (66). On the other hand, during a persistent infection of rats by MHV, the S gene was reported to be stable, arguing in this case against the emergence of quasispecies (75). The generation of diverse genomic populations during a persistent infection could depend on host factors, explaining differences observed between mice and rats.…”
Section: Discussionmentioning
confidence: 94%
“…However, no specific mutation was necessary for the establishment of in vivo persistence (66), even though a variety of mutations in the N and S genes was observed in mice, suggesting the development of quasispecies (66). On the other hand, during a persistent infection of rats by MHV, the S gene was reported to be stable, arguing in this case against the emergence of quasispecies (75). The generation of diverse genomic populations during a persistent infection could depend on host factors, explaining differences observed between mice and rats.…”
Section: Discussionmentioning
confidence: 94%
“…A controversy has arisen in recent scientific publications concerning the possible emergence of quasispecies during per-sistent coronavirus infections within the CNS. Stühler and colleagues reported that no quasispecies arose during a persistent MHV-JHM infection within the CNS of rats (68). Moreover, another study showed little evidence for the selection of specific mutations within the M protein, N-cytotoxic-T-lymphocyte epitope, and encapsidation sequence with time after infection in mice (6).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of persistence on virus population dynamics is almost unknown. In one study of mouse hepatitis virus no population variation was detected in persistent infections, contrasting with acute infections that have a quasispecies nature [45]. This is an intriguing finding that merits some thought.…”
Section: Persistent Virusesmentioning
confidence: 97%